Four FATCO syndrome cases: clinical, autopsy and placental features with literature review update - Francisco Valente, PurificaÃƒÂ§ÃƒÂ£o Tavares, Rosete Nogueira, Joaquim SÃƒÂ¡, Catarina Varela, GraÃƒ (Journal of Medical Biomedical and Applied Sciences, 2016)
Fibular Aplasia-Tibial Campomelia-Oligosyndactyly, or FATCO, is a rare syndromic condition reported in 18 cases so far, from which only 3 were diagnosed at prenatal stages. In this study we report comprehensive clinical, placental and autopsy findings of four additional prenatal cases of FATCO, with the aim of further delineating this syndromic condition. Understanding this disorder at prenatal stages will allow for an earlier diagnosis through the identification of key features, thus permitting an adequate parental counselling about the pregnancy development.